The role of Algerian diplomacy in the Libyan crisis: Objectives and obstacles - Guattas, Samir; Benaissa, Lazhar (Technium Social Sciences Journal, 2022)
This article aims to analyse the position of Algerian diplomacy with regard to the Libyan crisis and the attempts to resolve this fratricidal conflict, which has become an economic and security burden for Algeria. Where, the Libyan crisis, due to the proximity of this country to Algeria, has become a source of threats and protean (security) risks, a fortiori terrorism. It should be noted that Algeria's diplomatic approach is based on a "political solution" to the Libyan crisis, which consists of banning any form of foreign intervention, especially military. This approach has come up against the complexity of the Libyan reality and its regional and international ramifications. In this article, we address the following elements - the evolution of the Algerian diplomatic position towards the Libyan crisis since 2011; - the nature of the Algerian diplomatic preoccupation towards the Libyan crisis. We will also try to analyse the deeper issue of the balance between the moral (or principled) dimension versus strategic interests of Algerian diplomacy in the Libyan crisis. Finally, we will try to provide a prospective vision of the possible future paths of Algerian mediation in the Libyan crisis.